Living standards since the last election - Tom Wernham; Sam Ray-Chaudhuri; Tom Waters (Institute for Fiscal Studies (IFS), 2024)
New income statistics suggest this parliament is on course to be the worst for living standards on record.
Keywords: 330; Employment and income; Poverty; inequality and social mobility; Election 2024; Inequality; Inflation; Living standards; Poverty